2023
DOI: 10.1101/2023.01.30.526359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The defects of the hippocampal ripples and theta rhythm in depression, and the effects of physical exercise on their amelioration

Abstract: The pathophysiology of depression remains elusive, and its early diagnostic method has not been established. Accumulated evidence demonstrate that environmental stress affects the hippocampus, functioning in cognition and sociality, and causes various depressive symptoms. In addition, recent findings showed that environmental stress influenced the hippocampal activity correlated with neuroinflammation, and impaired the hippocampal sharp wave ripples (SWRs), pattens of spike sequences, and the theta rhythms, a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…63) Moreover, chronic restraint stress depresses the occurrence and magnitude of hippocampal ripples, but this attenuation is rescued by physical exercise in a cage with running wheels. 68) Surprisingly, we demonstrated that short-term preexposure to the novel EE increased the frequency of ripple events in urethane-anesthetized mice, although most hippocampal ripples are likely to be abolished under anesthesia. Chronic exposure of mice to the EE modulates sharp wave-ripple complexes under in vitro conditions, 69) but few studies have explicitly reported an effect of short-term EE-exposure on hippocampal ripples; note that acute EEexposure adds to ripples during subsequent recording in the awake state.…”
Section: Discussionmentioning
confidence: 72%
“…63) Moreover, chronic restraint stress depresses the occurrence and magnitude of hippocampal ripples, but this attenuation is rescued by physical exercise in a cage with running wheels. 68) Surprisingly, we demonstrated that short-term preexposure to the novel EE increased the frequency of ripple events in urethane-anesthetized mice, although most hippocampal ripples are likely to be abolished under anesthesia. Chronic exposure of mice to the EE modulates sharp wave-ripple complexes under in vitro conditions, 69) but few studies have explicitly reported an effect of short-term EE-exposure on hippocampal ripples; note that acute EEexposure adds to ripples during subsequent recording in the awake state.…”
Section: Discussionmentioning
confidence: 72%